Amorphous/Crystalline Heterophase Ruthenium Nanosheets for pH‐Universal Hydrogen Evolution. Issue 3 (26th December 2021) - Xu, Jie; Kong, Xiangkai
Abstract: To design and synthesize heterophase noble‐metal materials is of crucial importance owing to their unique structure and apparent properties. Ruthenium (Ru) is one of the most active candidates for hydrogen evolution reaction because of its low price compared with other precious metals, which is favorable for industrial hydrogen cycle operation. In this study, free‐standing amorphous/crystalline Ru nanosheets are facilely synthesized through a controlled annealing method. Charge redistribution occurs at the phase interface because of the work function difference between amorphous and crystalline domains. The resulting structure and property are conductive to the adsorption and dissociation of water molecules, associated with optimized hydrogen interaction and enhanced binding between Ru atoms. Accordingly, electrochemical measurements demonstrate that the amorphous/crystalline heterophase Ru exhibits improved hydrogen evolution efficiency as compared with pure amorphous Ru and pure crystalline Ru, at pH‐universal conditions. Specifically, only 16.7 mV overpotential is required to reach 10 mA cm −2 in 1.0 m KOH. Meanwhile, the heterophase structure displays a higher stability during operation than pure amorphous and crystalline structures. This study demonstrates the importance of phase engineering, broadens the Ru‐based material family, and provides more insights for developing efficient metal materials. Abstract : Free‐standing Ru nanosheets with amorphous/crystalline heterophases are successfully synthesized, which outperform both of their amorphous and crystalline counterparts during the hydrogen evolution reaction (HER) in pH‐universal electrolytes. The formation of interphase is the key to increase the HER performance. Meanwhile, the amorphous/crystalline heterophase structure also shows improved stability when compared with its pure amorphous and crystalline counterparts.